Short Communication: Herpetofauna diversity at the University of Palangka Raya, Indonesia - Andri Maulidi; Titin Purnaningsih; Anita Maulina; Yohanes Edy Gunawan; Muhammad Rizki (Society for Indonesian Biodiversity, 2020)
Abstract. Maulidi A, Purnaningsih T, Maulina A, Gunawan YE, Rizki M. 2020. Short Communication: Herpetofauna diversity at University of Palangka Raya, Indonesia. Biodiversitas 21: 4509-4514. Research on herpetofauna at the University of Palangka Raya (UPR) is vital as there has been no official data so far and remains to be anecdotal evidence from various members of the university. The present study aimed to analyze and report the herpetofauna diversity on the Tunjung Nyaho Campus. It was conducted between October 2019 and November 2019. Herpetofauna data were collected using the Visual Encounter Survey (VES) method. Diurnal and nocturnal surveys were carried out between 07:00-10:00 and 19:00-22:00, respectively. The results showed that as many as 12 species of herpetofauna were present, including six species of reptiles from six families and six species of amphibians from four families. Comparative diversity analyses of these species, unburned, post-burnt, and around building, indicated that the unburned area had a relatively high diversity (2.06) compared to the other two (0.86 and 0.88, respectively). However, the evenness index (E) for the herpetofauna community in all three locations was > 0.70. The resulting species list from this study consisted of two species with threatened statuses under the IUCN Red List, i.e., Ophiophagus hannah (VU), and Cuora amboinensis (EN).